Influence of marital discord, separation and divorce on poor academic performance of undergraduate students of University of Ibadan (2011)
The study investigated the influence of marital discord, parental separation and divorce on the academic performance of undergraduate students of the University of Ibadan. A total of 400 students were randomly selected from 8 Faculties on the basis of convenience and availability. All participants' present Cumulative Grade Point Average (CGPA) stands at 2.5 and below, which is a clear manifestation of poor academic performance. The participants responded to a validated questionnaire on parental marital discord, separation and divorce. Four research hypotheses were generated and tested at 0.05 level of significance. The findings revealed that significant difference exists between the academic performance of students from undisrupted homes and their counterparts from disrupted homes, t (398) =5.824, P < 0.05. The mean of the academic performance of students from undisrupted homes (56. 18) is taken to be better than the mean for those from disrupted homes( 52.93). Also, significant relationship exists between academic performance and parental marital discord (r = -0.109), academic performance and parental separation (r =-0.198), and finally, academic performance and parental divorce (r = -6.226). It was therefore recommended that married individuals should endeavour to stay together for the sake of their children academic pursuits. Couples should be trained in acquisition of marital conflicts skills. Openness to each other, forgiveness, understanding and ability for couples to clothe themselves with love are all recommended